Forests, environment and tribal economy - Fernandes, Walter; Menon,Geeta; Viegas,Philip (New Delhi, 1988)
With the tree cover in the country coming down to 10 per cent, efforts are being made to fix responsibility for the destruction of the country's forests. While some official agencies as well as urban environmentalists accuse the people of being destroyers of forests, others have been claiming that industry. has to be considered the culprit. Where does the truth lie? That was the starting point of this study. It looks at the forest from the point of view of the people, studies the extent of their dependence, the role of minor forest produce, shifting cultivation and firewood in their economy. It analyses the position of commercialisation and of middlemen and identifies the factors that have helped the tribals to preserve forests for centuries. Based on this understanding, the study analyses the causes of deforestation, official and people's solutions and the interests behind them. Based on this understanding, the authors have their own suggestions to make. This is thus a pioneering study that gives a new dimension to the national debate on the Forest Policy and tribals.
Keywords: Forestry-India